Learning Loss in Speaking Skill from Psychology Point of View - Siti Aisyah; Yuli Tiarina (Journal of English Language Teaching, 2023)
The purpose of this study is to describe the impact of learning loss on the psychological condition of students in the speaking class of the Department of English Education, Faculty of Language and Arts, Universitas Negeri Padang during the Corona Pandemic. The design of this research is descriptive research. The population for this study was all first-year students of the 2021 academic year of the Department of English Education, Faculty of Languages and Arts, Universitas Negeri Padang and the sample was 22 students from the international class. This study used an online questionnaire and the questionnaire was made of close-ended questions. The most used platforms by students and lecturers are LMS/E-Learning and Zoom Meeting. Students do not experience learning loss in terms of student psychology because students can master learning and reflect on it during online learning, and students can adapt to learning changes that occur due to the pandemic, students master the knowledge and can reflect on the learning process, and students can associate new information with relevant concepts in their cognitive structure. Learning loss has no impact on students' psychological conditions. Learning loss does not have an impact on students because students have ways to overcome the psychological stress that arises during online learning and students who have a high level of resilience in dealing with their problems have a smaller risk of experiencing depression. Students with a high level of resilience will recover faster from pressure and cope with their problems more actively.